The prospect of Web 2.0 in China - Wei, Zhu (2010)
The Internet is stepping in a new stage of its development. More and more applications are making the Internet a new face. Nowadays, a new conception is attracting attention in the world which is web2.0. It is not a simple conception or term but a new idea and a new Internet application philosophy. People use this idea to distinguish the Internet social system, web service and application. We will conduct research on the conception and phenomenon of Web 2.0 and analyze a great amount of applications and related webs of typical Web2.0. In this essay, we will address the structure, analysis and discussion of Web 2.0. We also make research and show the application, related operation model and business model in China on the basis of web 2.0. We put forward the new thinking and advice, forecast the development trend and the influence to the Internet.